The Effect of Using Glucomannan Flour and Carageenan on The Manufacture of Jelly Candy - Juliastuti, Sri Rachmania; Meliyati, Hartinah; Machmud, Glenn Mochamad Rayhan (LPPM, Institut Teknologi Sepuluh Nopember, Indonesia, 2024)
Indonesia is one of the countries that produces porang tubers in the world The biggest benefit of cultivating porang plants is to obtain the tubers. The harvested porang tubers can be sliced or chipped and then dried. Porang slices or chips can then be processed into konjac flour or konyaku. From konjac flour, glucomannan can be obtained. The aim of this research is to make jelly candy from porang flour which will be purified first by an extraction process using ethanol. The research method used was to extract 70 g of porang flour using foodgrade ethanol with a concentration of 50% as much as 560 ml by stirring on a hotplate at 30 ℃, stirring speed of 600 rpm and stirring time ( 30 minutes, 60 minutes, 90 minutes) which will then be filtered to obtain porang flour precipitate then in the oven for 12 hours with a temperature of 90 ℃. From the research results, it was found that the best glucomannan content was at a stirring speed of 600 rpm for 60 minutes, namely 81,52 %. Then, the best results of glucomannan flour were applied by being used as an ingredient for making jelly candy added to carrageenan.